Manajemen Kinerja UKM di Era Transformasi Digital: Systematic Literature Review Anteseden, Moderator dan Mediator - Rosalina, Dhian; Sugianto; M Shabri Abd Majid (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
Digital transformation has become a major driving force behind changes in management practices and the performance of Small and Medium Enterprises (SMEs). This study aims to identify and map the factors influencing SME performance through a Systematic Literature Review (SLR) using the PRISMA method based on 30 scientific articles indexed in Scopus and Sinta. The review focuses on three primary constructs: antecedents, moderators, and mediators that contribute to enhancing the performance of small and medium-sized enterprises (SMEs). The findings categorize antecedents into five major groups: human resources, organizational strategy, organizational context, innovation, and learning Knowledge. Among these, human resources emerge as the most frequently cited factor affecting SME performance. Furthermore, innovation, dynamic capabilities, digital and financial literacy, and motivation are identified as key mediating variables that bridge the influence of antecedents on performance. On the other hand, moderators such as international mindset, technological dynamism, and organizational capability can strengthen or weaken these relationships. This study emphasizes the need for a holistic approach to improving SME performance and offers theoretical and practical implications for future research and SME development policies in the digital era